Closure of a Recurrent Urethrovaginal Fistula in a Girl with Cloacal Anomaly Using Deflux Injection - Hanan Said; Salahuddin S. Syed; Ali Zeinelabdeen; Mohamed Negm Fayez (Georg Thieme Verlag KG, 2018)
In a girl born with cloaca, both hemivaginae and rectum were located above the bladder neck, and both ureters were connected to the hemivaginae. After diverting colostomy and cystovaginoscopy on the second day of life, the repair of cloaca was performed at 10 months of age by posterior sagittal anorecto vaginoplasty (PSARVP), including laparotomy and bilateral ureteric reimplantation. Eight months after the surgery, she developed a vesicovaginal fistula, which was repaired and closed by open surgery through the bladder. Three months after this procedure, a tiny urethrovaginal fistula was noticed, which was closed at the age of 2 years using hook diathermy to refresh the edges and was then closed by Deflux injection. The proper closure of the urethrovaginal fistula was confirmed by radiology and cystoscopy 3 months after the surgery. This report shows that injection of Deflux into a tiny urethrovaginal fistula following refreshing the edges may be a valid treatment option in selected cases.